2019
DOI: 10.1080/17453674.2019.1607111
|View full text |Cite
|
Sign up to set email alerts
|

Hip-fracture osteosynthesis training: exploring learning curves and setting proficiency standards

Abstract: Background and purpose — Orthopedic surgeons must be able to perform internal fixation of proximal femoral fractures early in their career, but inexperienced trainees prolong surgery and cause increased reoperation rates. Simulation-based virtual reality (VR) training has been proposed to overcome the initial steep part of the learning curve but it is unknown how much simulation training is necessary before trainees can progress to supervised surgery on patients. We determined characteristics of learning curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…In contrast to previous studies with the simulator, this study is the first to include clinical variability in the simulation program. Previous studies have considered the validity of the simulator and explored learning curves of repetitively operating on the same side of a single patient (Pedersen et al 2014 , Akhtar et al 2015 , Sugand et al 2015 , Gustafsson et al 2019 ). We strongly believe that the introduction of clinical complexity is essential to exploit the full learning potential of the VR simulation program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies with the simulator, this study is the first to include clinical variability in the simulation program. Previous studies have considered the validity of the simulator and explored learning curves of repetitively operating on the same side of a single patient (Pedersen et al 2014 , Akhtar et al 2015 , Sugand et al 2015 , Gustafsson et al 2019 ). We strongly believe that the introduction of clinical complexity is essential to exploit the full learning potential of the VR simulation program.…”
Section: Discussionmentioning
confidence: 99%
“…The construct validity of the virtual reality (VR) simulator (TraumaVision, Swemac Simulation AB, Sweden) has been established, i.e., the simulator performance correlates with surgical experience (Pedersen et al 2014 , Akhtar et al 2015 , Gustafsson et al 2019 ). Notably, the simulator can discriminate between novices (< 10 DHS), intermediates, and experts (Akhtar et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten cases was chosen because previous learning curve analysis of trainees performing simulated hip fracture osteosynthesis suggests that around ten repetitions are required for performance to stabilize in the associative learning phase. 23 For continuous outcomes, we compared the means between both groups using t -test, and tested whether the difference between groups was zero. For categorical outcomes, we conducted a chi-squared test of association, or Fisher’s exact test if cell counts were less than five.…”
Section: Methodsmentioning
confidence: 99%
“…Virtual reality (VR) simulation training has been introduced to address the issue of training, and previous studies have demonstrated that VR simulation training can ensure basic proficiency of the junior surgeon before continued supervised clinical training [2, 3]. Consequently, VR simulation in hip fracture surgery is available to Danish orthopedic residents at an early stage of their training.…”
Section: Introductionmentioning
confidence: 99%